(3cJGH aj GdadGMIs - (3GHf GdYhGe GdGTHjdj , jMji Hf eMeO Hf CMeO Hf GdYhGe GdGTHjdj, CHh RcQjG,J (B580 (3g` s
(3ChdgG (B:s
(3CeG HYO aEfi deG bQCJ ef cJH GdadGMI GdeSdejf s
(3BNQgG (B:s
(3Je GdSaQ GdKGi ef cJGH GdadGMI ai GdCQVjf hGdMjhGf s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B165 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B222s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B320s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdRQGYI h GdCYTGHs